Proprotein Convertase Subtilisin/Kexin Type 9 Inhibition: A New Therapeutic Mechanism for Reducing Cardiovascular Disease Risk. Issue 17 (27th October 2015) - Bergeron, Nathalie; Phan, Binh An P.; Ding, Yunchen; Fong, Aleyna; Krauss, Ronald M.
Abstract : Proprotein convertase subtilisin/kexin type 9 (PCSK9) plays an important role in the regulation of cholesterol homeostasis. By binding to hepatic low-density lipoprotein (LDL) receptors and promoting their lysosomal degradation, PCSK9 reduces LDL uptake, leading to an increase in LDL cholesterol concentrations. Gain-of-function mutations in PCSK9 associated with high LDL cholesterol and premature cardiovascular disease have been causally implicated in the pathophysiology of autosomal-dominant familial hypercholesterolemia. In contrast, the more commonly expressed loss-of-function mutations in PCSK9 are associated with reduced LDL cholesterol and cardiovascular disease risk. The development of therapeutic approaches that inhibit PCSK9 function has therefore attracted considerable attention from clinicians and the pharmaceutical industry for the management of hypercholesterolemia and its associated cardiovascular disease risk. This review summarizes the effects of PCSK9 on hepatic and intestinal lipid metabolism and the more recently explored functions of PCSK9 in extrahepatic tissues. Therapeutic approaches that prevent interaction of PCSK9 with hepatic LDL receptors (monoclonal antibodies, mimetic peptides), inhibit PCSK9 synthesis in the endoplasmic reticulum (antisense oligonucleotides, siRNAs), and interfere with PCSK9 function (small molecules) are also described. Finally, clinical trials testing the safety and efficacy of monoclonal antibodies to PCSK9 are reviewed. These have shown dose-dependent decreases in LDL cholesterol (44%–65%), apolipoprotein B (48%–59%), and lipoprotein(a) (27%–50%) without major adverse effects in various high-risk patient categories, including those with statin intolerance. Initial reports from 2 of these trials have indicated the expected reduction in cardiovascular events. Hence, inhibition of PCSK9 holds considerable promise as a therapeutic option for decreasing cardiovascular disease risk.